Compare the Effectiveness in Term of Attenuating Stress Response between Oral Pregablin and Intravenous Lignocaine in Patients with Hypertension (Medical Forum Monthly, 2020)
Objective: To compare the efficacy of oral pregablin with intravenous lignocaine in term of attenuating pressor response in patients presented with hypertension.Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the Main Operation Theatre DHQ Teaching Hospital/ Gujranwala Medical College, Gujranwala and Anaesthesia Department PIC, Lahore from October 2019 to February 2020.Materials and Methods: One hundred and four hypertensive patients of both genders with ages 20 to 65 years undergoing elective surgeries were enrolled in this study. All the patients were equally divided into two groups, each group contains 52 patients. Group I received oral pregablin and group II received IV lignocaine. Heart rate, systolic BP and diastolic BP were examined before and after intubation between both groups.Results: No significant difference was observed between both groups regarding age, sex and body mass index (BMI) with p-value >0.05. Before intubation no significant difference was observed regarding heart rate, systolic and diastolic BP. A significant lower heart rate was found in group I after intubation 91.28±12.66 beat/min as compared to group II 97.86±13.44 (p-value <0.05). In group I mean systolic BP and diastolic BP after intubation were significantly lower than the group II with p-value <0.05.Conclusion: Oral pregablin had better efficacy for attenuating stress response as compared to intravenous lignocaine in patients with hypertension.